Association between the intake of potentially risky beverages and the occurrence of endometrial polyps: a case–control study - Rui Fu; Rui Fu; Shipeng Zhang; Shipeng Zhang; Chang Cai; Chang Cai; Xiaocui Wang; Xiaocui Wang; Yanjie Jiang; Xiulian Zhuang; Xiulian Zhuang; Jiating Zhang; et al. (Frontiers in Nutrition)
BackgroundThis case–control study aimed to examine the association between the frequency of potentially risky beverage consumption, levels of anxiety, and the prevalence of endometrial polyps.MethodsA total of 418 participants were enrolled in the study, comprising 206 cases and 212 controls. The case group consisted of patients who visited the gynecological clinic at the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine and were diagnosed with endometrial polyps (Eps) based on international diagnostic criteria. The control group consisted of women of childbearing age who visited the gynecological clinic with similar clinical symptoms but did not have EPs. Basic information, consumption of potentially risky beverages (PRB), and anxiety levels for both groups were collected through a questionnaire survey. Finally, the relationship between the frequency of PRB consumption, anxiety levels, and the prevalence of EPs was evaluated.ResultsIn this study, we identified a significant positive association between the consumption of PRB and the prevalence of EPs. PRB intake was categorized into three groups based on the cumulative total score: 5–8 for the Low potentially risky beverages (LPRB) intake group, 9–12 for the medium potentially risky beverages (MPRB) intake group, and 13–21 for the high potentially risky beverages (HPRB) intake group. The results revealed that PRB consumption frequency was significantly associated with EPs (OR: 2.348, 95% CI: 1.153–4.78), with higher PRB intake correlating with an increased risk of EPs (p-value: 0.014). However, no significant difference was observed between the LPRB, MPRB, HPRB intake frequency groups and the different levels of anxiety (p-value: 0.793).ConclusionIncreased consumption of PRB was clearly associated with a greater risk of EPs, and over half of the participants exhibited varying degrees of anxiety. These findings suggest that the risk of EPs can be mitigated by controlling beverage intake and highlight the need for increased attention to women’s mental health.Clinical trial registrationNCT06295510.